Transcriptional regulation of macrophage cholesterol trafficking by PPARα and LXR. (25th October 2006) - Chinetti, G.; Fruchart, J.C.; Staels, B.
Abstract : PPARs (peroxisome-proliferator-activated receptors) and LXRs (liver X receptors) are ligand-activated transcription factors that control lipid and glucose metabolism, as well as the inflammatory response. Since the macrophage plays an important role in host defence and immuno-inflammatory pathologies, particular attention has been paid to the role of PPARs and LXRs in the control of macrophage gene expression and function. Altered macrophage functions contribute to the pathogenesis of many infectious, immunological and inflammatory disease processes, including atherosclerosis. Research over the last few years has revealed important roles for PPARs and LXRs in macrophage inflammation and cholesterol homoeostasis with consequences in atherosclerosis development. This review will discuss the role of these transcription factors in the control of cholesterol trafficking in macrophages.